Antimicrobial Photodynamic Therapy mediated by Photodithazine® in the treatment of denture stomatitis: A case report - Alves, Fernanda [UNESP]; Alonso, Gabriela Caroline [UNESP]; Carmello, Juliana Cabrini [UNESP]; Mima, Ewerton Garcia de Oliveira [UNESP]; Bagnato, Vanderlei Salvador; Pavarina, Ana Cláudia [UNESP] (Elsevier, 2018)
Antimicrobial Photodynamic Therapy (aPDT) mediated by Photodithazine® (PDZ) has shown efficacy in the inactivation of Candida spp. in in vitro and in vivo studies. This preliminary study reports five clinical cases of patients with denture stomatitis (DS) treated with PDZ-mediated aPDT. Five individuals diagnosed with DS were selected and submitted to aPDT 3 times a week for 15 days (6 sessions). In each session, 200 mg/L of PDZ gel was applied on the upper prostheses and on the palate of the patients for 20 min, then, illuminated by a light emitting diode at 660 nm (50 J/cm2). Microbiological samples from prostheses and palates were also performed and cultured on Sabouraud Dextrose Agar and Blood Agar. The values ​​of colony forming units per milliliter (CFU/mL) were determined. Standardized photographs of the palates were taken prior the treatment (initial), at the end (final) and until 45 days after the completion of treatments. The results demonstrated that the aPDT treatment reduced Candida spp. and the total microbiota viability ​​at the end of the treatment. For most patients, the CFU/mL values obtained in the last microbiological collection (day 45) were lower than those found before the treatment (initial). Three patients presented clinical resolution of DS (no DS signal) after aPDT treatment. One individual demonstrated reduction in palatal inflammation and another one did not show improvement in the oral lesion. Recurrence of DS was observed in all individuals in the follow-up period. PDZ-mediated aPDT may be a promising treatment for DS.
Keywords: Antimicrobial photochemotherapy; Candida; Oral candidiasis